TINJAUAN PROSEDUR PENAGIHAN PIUTANG PADA PT ALTERNATIVE MEDIA GROUP - Lalita Ayurahma Abidin (2022)
Through this final project, the author has the aim of learning more about the procedures for collecting receivables at PT Altenative Media group and the specific purpose of writing this final project is as one of the requirements for graduation from the Diploma III program for the accounting major, Universitas Pembangunan Nasional Veterans Jakarta. In a company engaged in digital advertising media, PT Alternative Media Group provides services in the form of showing advertisements in public places targeting people who carry out activities outside the home. Procedure is a flow that must be carried out by each division with the aim of avoiding errors or fraud that can harm the company. Customers who will use advertising services at PT Altenative Media Group are expected to make payments according to the agreed maturity date. Accounts receivable in a company include the largest element of the company's total assets. If the debtor does not fulfill his obligation to pay, the company will accept the risk of loss. That way doing good procedures in collecting receivables is part of an effort to avoid company losses. In the collection of receivables, supporting documents that serve as evidence for collection of receivables include, among others, Approval Package, Media Order, Log Proof, Tax Invoice, Invoice, Documentation Evidence, Minutes of Handover, Minutes of Work Completion, and Cooperation Agreements.